Fashion thinking - Dieffenbacher, Fiona (Required reading range. Course reader., 2013)
Students often struggle to develop their own style and approach to design. While the design process is fundamental to the way all fashion designers work, there is no right or wrong method: each emerging designer must find their own authentic process. This book establishes key approaches to design and enables this process of discovery. Nine student projects form the core of the book, representing a diverse range of strategies at each key stage of the design cycle. By following each throughout their various stages of development, these examples offer a unique and inspiring insight into the thinking behind a final collection.